METHOD OF INTELLIGENT RECOURCE MANAGEMENT OF TELEMEDICAL SYSTEMS - Семко, Олексій; Семко, Віктор (SWorldJournal, 2025)
In telemedical systems and computer networks, communication networks of heterogeneous topological structure are currently becoming more widespread, which include subsystems for transmitting, accumulating and processing information using wired and wireless